Physical And Electromagnetic Properties Of Tm And Gd Substituted Mg-Mn Ferrites - Lwin, Nilar (2013)
In this work, magnesium ferrite was firstly fabricated by citrate precursor method (CPM) and solution combustion method (SCM). The structural, morphological, and electromagnetic magnetic properties of the ferrites from both methods were investigated. Using CPM, a single phase and nano-sized (10-15 nm) MgFe2O4 ferrite was formed at 500oC as evidenced from XRD analysis of the synthesized powders. On the other hand, SCM had produced single phase ferrite with nanosize of (8-9 nm) at around 200oC. Subsequently, SCM was chosen to produce Mg0.9Mn0.1Fe2-xO4 with x=0.2, 0.4, 0.6 and 0.8 to determine the effect of varying Fe content. The XRD analysis confirms that all the specimens showed the presence of cubic spinel phase. In terms of properties, the resistivity was observed to increase when Fe content were reduced. The Mg0.9Mn0.1Fe2-xO4 was found to show highest density (4.26 g/cm3), dielectric constant (11.136), higher resistivity, and a high saturation magnetization (38.41 emu/g). Then, using this compostion as the base, Tm substitution was performed and this was found to produce a secondary phase TmFeO3. It was also found that the physical and magnetic properties had changed with Tm content. Bulk density was found to decrease from 4.26 to 3.82 g/cm3 with increasing Tm. From the magnetic properties, it was found that saturation magnetization had decreased with increase of Tm. Highest resistivity (39.84 x 106 Ω-cm) was observed for Mg0.9Mn0.1Fe1.725Tm0.075O4. Besides Tm substitution, the effect of Gd substitution on structural and electromagnetic properties of ferrite was also investigated. The substitution of Gd had easily formed secondary phase at grain boundaries.